DESIGN OF FILTER FOR SIX PULSE CONVERTER - Gandhi, Kapil; Ali, Maroof; Saxena, Saurabh (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Non-linear loads produce harmonic currents that can travel to other locations in the power system and eventually back to the source. Harmonic currents can produce a variety of effects that are harmful to the power system. Harmonic currents are a result of the characteristics of particular loads. As long as we choose to employ those loads, we must deal with the reality that harmonic currents produced by a non-linear current source will not unduly interfere with the rest of the power system is to filter out the harmonics. Application of harmonic filters helps to accomplish this